Methamphetamine enhances caveolar transport of therapeutic agents across the rodent blood-brain barrier - Campbell, Matthew (My University, 2022)
The blood-brain barrier (BBB) restricts clinically relevant accumulation of many therapeutics in the CNS. Low-dose methamphetamine (METH) induces fluid-phase transcytosis across BBB endothelial cells in vitro and could be used to enhance CNS drug delivery. Here, we show that low-dose METH induces significant BBB leakage in rodents ex vivo and in vivo. Notably, METH leaves tight junctions intact and induces transient leakage via caveolar transport, which is suppressed at 4C and in caveolin-1 (CAV1) knockout mice. METH enhances brain penetration of both small therapeutic molecules, such as doxorubicin (DOX), and large pro- teins. Lastly, METH improves the therapeutic efficacy of DOX in a mouse model of glioblastoma, as measured by a 25% increase in median survival time and a significant reduction in satellite lesions. Collectively, our data indicate that caveolar transport at the adult BBB is agonist inducible and that METH can enhance drug delivery to the CNS.
PUBLISHED
cited By 1